2015
DOI: 10.1155/2015/245625
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Copolymeric Resveratrol Conjugates

Abstract: Resveratrol (RSV), naturally found in plants, is known to have health benefits and has been proposed as a potential anticancer and cardioprotective drug. However, due to its molecular structure, it undergoes rapid metabolism in the body resulting in low bioavailability. Novel polymeric methoxy-poly(ethylene glycol)-block-poly(ε-caprolactone) (mPEG-PCL) RSV conjugates with varying PCL chain lengths have been synthesised and formulated into micelles and/or nanoparticles for preliminaryin vitrostability studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Hsu et al found that the combination of resveratrol with kefir could reduce fatigue and improve exercise performance in mice when administered as a food supplement [9]. Resveratrol has been successfully combined with other protective chemical groups [10,11]. Mattarei et al prepared amino acid carbamates as resveratrol prodrugs.…”
Section: Introductionmentioning
confidence: 99%
“…Hsu et al found that the combination of resveratrol with kefir could reduce fatigue and improve exercise performance in mice when administered as a food supplement [9]. Resveratrol has been successfully combined with other protective chemical groups [10,11]. Mattarei et al prepared amino acid carbamates as resveratrol prodrugs.…”
Section: Introductionmentioning
confidence: 99%